Mopin and its Sacred Ritualistic Aspects - Eli Doye (Dera Natung Government College Research Journal)
This fieldwork-based article provides an ethnographic overview of the Mopin festival of the Galos and its underlying ritualistic aspects. The Galos have a rich, multi-faceted and distinct culture of their own. Among the diverse types of traditional cultural expressions (TCEs) of the Galo tribe, Mopin is the most popular and significant. In fact, it forms a part of the identity and heritage of the indigenous community. Mopin has certain established sacred and religious rituals which are usually accompanied by hymns and incantations chanted by the nyibo (priests) and the bo (co-priests) from their memory. Regrettably, due to modern education and the influence of other religions especially Christianity, rituals associated with Mopin have undergone immense changes in the contemporary time.